Selective Skeletal Surveys for Infants With Skull Fractures: Examining the Rates of Return to Medical Care for Concern of Physical Abuse. Issue 12 (10th December 2022) - Dominguez, Michelle M.; Moore, Jessica L.; Cook, Megan; Rogers, Michelle L.; McCarten, Kathleen; Slingsby, Brett
Abstract : Objectives: This study aimed to describe which infants with a skull fracture (1) receive a child abuse pediatrician (CAP) consultation, (2) receive a skeletal survey, and (3) re-present to medical care before age 3 years with concerns for physical abuse. Methods: We conducted a retrospective chart review of infants younger than 12 months who presented to the emergency department between January 1, 2005, and December 30, 2015, with a skull fracture. Medical records were reviewed for the skull fracture presentation and for all future medical evaluations at the same institution with concerns for physical abuse until 3 years of age. Results: Of 366 infants with a skull fracture, a CAP was contacted for 272 (74%) and 76 (20.8%) infants who received a skeletal survey. Factors associated with skeletal survey acquisition included younger age (<6 months), no history to explain the skull fracture, other injuries on examination, and social risk factors. Six children (1.6%) re-presented to medical care with concerns of physical abuse before age 3 years. Five of these infants did not have a skeletal survey at the time of their skull fracture, and 1 was likely a case of missed physical abuse at the time of the skull fracture. Discussion: Most skull fractures in infancy occur accidentally, and a skeletal survey may not be necessary for every infant. Obtaining a thorough history including social risk factors, performing a complete physical examination, and consulting with a CAP is an effective first step in the evaluation of physical abuse in infants with skull fractures.